Transformasi Sosial: Pengabdian Masyarakat dalam Sosialisasi UU Batas Usia Perkawinan di Kecamatan Cilengkrang Kabupaten Bandung - Sopha Hafitriani; Azhar Muhammad Akbar; Yudi Daryadi; Abid Naufal Habibburokhman; Neng Siti Fatimah; Imay Nurrohmah; Imam Amin Tohirin (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
Early marriage is a significant social problem in Indonesia, including in Cilengkrang District, Bandung Regency. In an effort to address this problem, the Indonesian government issued Law Number 16 of 2019 which sets the minimum age of marriage to 19 years for both men and women. Community service in socializing this law in Cilengkrang Sub-district aims to increase community understanding and compliance with the regulation. The program involves various educational activities, such as counseling, group discussions, and training for community leaders and educators. The methods used include direct approaches through village meetings and indirect methods through social and print media. The results showed that the involvement of community leaders and religious leaders was very effective in conveying messages and reducing resistance to legal change. The main challenges faced were changing entrenched mindsets and problems accessing information in remote areas. Recommendations to improve the effectiveness of this program include increasing the involvement of community leaders, optimizing the use of media, continuous training, inter-agency cooperation, periodic evaluation, and a culturally sensitive approach. With the implementation of these recommendations, it is expected that the socialization of the marriage age limit law in Cilengkrang Sub-district can be more effective, reduce the number of early marriages, and create an environment that supports the optimal development of children and improves the overall welfare of the community.